A természet védelme, mint közvetlen morális imperatívusz Kant a Gyakorlati ész kritikája című művében - Miklovicz, Attila (Kultúratudományi Szemle, 2024)
The protection of nature as a direct moral imperative in Kant's Critique of Practical Reason Did Immanuel Kant consider the protection of the environment when he wrote his famous second critique, the Critique of Practical Reason. While the moral pressure of environmentalism was probably not yet present in 18th-century’s society, the author of this paper suggests that the direct imperative of saving the environment is traceable in Kant's central work on morality. By interpreting the directions Kant is giving to the application of the categorical imperative, the paper explains the role of nature in upholding human life and how morality is connected to that.